Pengembangan Media Pembelajaran Pop Up Book Guna Meningkatkan Pemahaman Materi Tumbuhan - Putri, Devy Ramadhani Dion; Syaufi, Shofa; Permatasari, Niken; Yuniar, Valentina Candra; Achmad , Nevialda Frisdiar (Nur Science Institute, 2022)
Background: This study aims to (1) develop students' understanding of plant material, (2) produce Pop Up Book learning media about plants, (3) find out the feasibility of Pop Up Book learning media on plant material for fourth grade students at SDN Badran 123. Method: The research design it is a research and development (R&D) method. The adaptation research development procedure is divided into 4 stages, namely the needs analysis stage, which is to examine the needs of learning media on plant material, the data collection stage to collect data references, the development stage is the process of making the required media based on the results of the needs analysis, and the product trial stage is carried out by 8 fourth grade students at SDN Badran 123. Data collection methods in this study used observation and interviews Result: the pilot interviews involving 8 grade 4 students at SDN Badran, the data obtained from the trial results on the Pop Up Book media were collected through student instrument sheets after media exposure. The total number of 6 questions in the percentage of students who answered (Yes) was 100% and students who answered (No) was a percentage of 0%. From these results it can be concluded that the use of Pop Up Book learning media about plant materials is very liked by students and they are very interested.. Implication: The implications of this study are: First, the elementary schools' headmasters in Indonesia should enrich the teachers' knowledge and insight related to learning medias. Second, the government, supported by researchers, has to design an excellent assessment system to solve time limitations. Novelty: The present study revealed the implementation of meida education in elementary school comprehensively.